MISSILES AND AIRCRAFT - PART 4 - Meyer, C. (Scientia Militaria - South African Journal of Military Studies, 2012)
This Article, the last of four concerning the role of air power in the Yom Kippur War, analysis the following: Missile effectiveness - (surface-to-air missiles, air-to-surface missiles, surface-to-surface missiles). Aerial combat and pilot training. Electronic warfare, Precision Guided Munitions and Remotely Piloted Vehicles. The use of satellites for real time intelligence.